Benefits of XML in Business. - Yi, Phoebe (XML journal :the ultimate enterprise resource.)
XML has become a hot topic over recent years due to its core qualities: extensibility, platform independence, and self-describing nature to name a few. Considered by many to solve a wide variety of a e-problems, it has enjoyed an optimistic following that believes it to be the next IT revolution, comparable to HTML